Методи та моделі управління контентом в розподілених інфокомунікаційних системах - Кирик, Мар’ян Іванович (Національний університет "Львівська політехніка", 2018)
Дисертаційну роботу присвячено проблематиці управління передаванням інформації в розподілених інфокомунікаційних системах та мережах доставки контенту з метою ефективного використання мережевих ресурсів глобальної інформаційної інфраструктури загалом, та її національного сегменту зокрема, шляхом підвищення продуктивності процесів передавання інформації в умовах збільшення її обсягів. В роботі представлено розв’язання проблеми розроблення методологічного забезпечення управління передаванням інформації в розподілених інфокомунікаційних системах та мережах доставки контенту з метою ефективного використання мережевої інфраструктури, підвищення системної продуктивності і якості надання послуг за рахунок динамічного балансування навантаження. Визначено критерії класифікації типів трафіку сучасних мультисервісних мереж та методику його ідентифікації, яка дозволяє отримати динамічну модель трафіку та адекватно підбирати алгоритми керування процесами передавання даних в інфокомунікаційних мережах. Запропоновано методи підвищення ефективності використання радіочастотного спектру та покращення параметрів якості надання мультисервісних послуг в когнітивній безпровідній мережі доступу із можливістю адаптивного налаштування параметрів обладнання та мінімізацією тривалості прийняття рішення про зміну радіочастотних каналів. Проведено дослідження технології передавання мультимедійного контенту, представлено концепцію та архітектуру мережі доставки контенту. Запропоновано механізми управління навантаженням в CDN-мережах для вибору оптимального маршруту його передавання та забезпечення заданої якості сервісу на основі впровадженої цільової функції. Запропоновано методологію синтезу мереж доставки контенту на основі сегменту глобальної мережевої інфраструктури, яка враховує методи ресурсного управління, наскрізного оцінювання їх параметрів, якості сервісу та стану активного мережевого обладнання, а також динамічного балансування навантаження, що дало змогу підвищити системну продуктивність та якість надання інфокомунікаційних послуг за рахунок ефективнішого використання мережевих ресурсів. Диссертационная работа посвящена проблеме управления передачей информации в распределенных инфокоммуникационных системах и сетях доставки контента с целью эффективного использования сетевых ресурсов глобальной информационной инфраструктуры в целом, и ее национального сегмента в частности, путем повышения производительности процессов передачи информации в условиях увеличения ее объемов. В работе представлено решение проблемы разработки методологического обеспечения управления передачей информации в распределенных инфокоммуникационных системах и сетях доставки контента с целью эффективного использования сетевой инфраструктуры, повышения системной производительности и качества предоставления услуг за счет динамической балансировки нагрузки. Определены критерии классификации типов трафика современных мультисервисных сетей и методика его идентификации, которая позволяет получить динамическую модель трафика и адекватно подбирать алгоритмы управления процессами передачи данных в инфокоммуникационных сетях. Предложены методы повышения эффективности использования радиочастотного спектра и улучшение параметров качества предоставления мультисервисных услуг в когнитивной беспроводной сети доступа с возможностью адаптивной настройки параметров оборудования и минимизацией длительности принятия решения об изменении радиочастотных каналов. Проведено исследование технологии передачи мультимедийного контента, представлена концепция и архитектура сети доставки контента. Предложены механизмы управления нагрузкой в CDN-сетях для выбора оптимального маршрута ее передачи и обеспечения заданного качества сервиса на основе внедренной целевой функции. Предложена методология синтеза сетей доставки контента на основе сегмента глобальной сетевой инфраструктуры, учитывающая методы ресурсного управления, сквозного оценивания их параметров, качества сервиса и состояния активного сетевого оборудования, а также динамической балансировки нагрузки, что позволило повысить системную производительность и качество предоставления инфокоммуникационных услуг за счет более эффективного использования сетевых ресурсов. The dissertation is devoted to the problems of information transfer management in distributed infocommunication systems and in content delivery networks in order to efficiently use network resources of entire global information infrastructure and its national segment in particular. It is reached by increasing the productivity of information transmission in conditions of its volumes growth. Management of multiservice streams requires using system models and algorithms of traffic management to optimize the performance of networks. The dissertation presents the solution to the problem of developing the methodological provision of information transmission control in distributed infocommunication systems and content delivery networks in order to effectively use the network infrastructure, increase the systemic productivity and quality of service delivery due to dynamic load balancing. In order to increase the productivity and efficiency of the information transmission control in the content delivery networks during content volume growth, there have been developed the model of self-similar multiservice traffic in distributed networks of streaming user load transmission as well as the mathematical model of probabilistic-time characteristics of the multiservice network. These models take into account the structural and functional features of the access level architecture. The criteria of traffic types classification in modern multiservice networks and traffic identification methods are determined. It allows to obtain a dynamic traffic model, which assists to select adequately the algorithms of transmission control in the infocommunication networks. The approaches that are used to determine the degree of self-similarity for network traffic are presented. The mathematical modeling was carried out to determine the quality of service parameters, which confirmed that the use of arbitrary methodology for calculating service quality parameters is inadmissible for traffic with self-similarity characteristic. The methods for increasing the efficiency of using the radio frequency spectrum and for improving the service quality in the cognitive wireless access network with the possibility of equipment parameters’ adaptive adjustment are proposed. As a result time used for decision on the change of radio frequency channels was redused. The multimedia content transmission technology, concept and architecture of the content delivery network are considered. The mechanisms of load management in CDN networks are proposed to choose the optimal route and provide quality of service with the usage of the contributed target function. The main load balancing methods are considered, which allow to rationally distribute the load between servers of the network and improve the quality of service. The system service model in wireless networks is presented, which should be used for efficient allocation of resources in a wireless environment. The simulation model for servicing queues of the multiservice network with the use of data prioritization was developed. A comparative analysis of the operation of queuing algorithms in wired and wireless networks for different types of streams was conducted. An algorithm for assessing the quality of service in the multiservice telecommunication network, which takes into account the work of several mechanisms of queuing and overload management was developed. The synthesis methodology of content delivery networks based on the segment of global network infrastructure was proposed. It takes into account resource management methods, cross-sectional evaluation of their parameters, quality of service and the state of active network equipment, as well as dynamic load balancing, which made it possible to increase the system productivity and quality of infocommunication services by more efficient use of network resources.
Методы и модели управления контентом в распределенных инфокоммуникационных системах
Methods and models for content management in distributed infocommunication systems
Keywords: мережі доставки контенту; CDN; інфокомунікації; глобальна інформаційна інфраструктура; управління трафіком; QoS; QoE; сети доставки контента; CDN; инфокомуникации; глобальная информационная инфраструктура; управление трафиком; QoS; QoE; Content Delivery Network; CDN; іnfocommunication; Global Information Infrastructure; traffic engineering; QoS; QoE; 621.391